Water quality analysis on the growth of seaweed (Kappaphycus alvarezii) off-bottom method, Ketapang District, South Lampung - Mulyono, Slamet; Susanto, Gregorius Nugroho; Riantini, Maya; Setyawan, Agus; Abidin, Zainal (Sangia Research Media and Publishing, 2025)
Seaweed Kaphapicus alvarezii is very popular in cultivation because it has high economic value and has quite large development potential in Ruguk Village, Ketapang District, South Lampung Regency. Water quality is a factor that influences the growth of seaweed, including the Kaphapicus alvarezii type, both physical and chemical water quality. This research aims to determine the condition of water quality in the seaweed cultivation area of Ruguk Village, Ketapang District, South Lampung Regency, meets the optimal living conditions for cultivating Kaphapicus alvarezii seaweed. This research is a type of descriptive research with a survey method carried out by taking water samples at seaweed cultivation locations and measuring the increase in seaweed growth every week for 4 weeks. The parameters observed in this research were the physical and chemical parameters of the water quality of the seaweed rearing media at the research location which consisted of temperature, brightness, current, pH, salinity, dissolved oxygen (DO), and phosphate and relative growth of the seaweed. Based on the results of observations during the research, it can be concluded that the water quality conditions, both physical and chemical water quality in the seaweed cultivation area in Ruguk Village, Ketapang District, South Lampung Regency, are in accordance with the standard quality requirements for the growth of Kaphapicus alvarezii seaweed, namely temperature 29.1-30.2⁰C, brightness 0,8-1.5 m, current strength 0.20-0.37m/sec, depth 0.8–1.5 m, pH 7.5-8.17, salinity 26-30 ppt, DO of 4.6-7.2 ppm, nitrate 0.2-0.92 mg/L and phosphate of 0.258-0.711 mg /L